Artificial shear stress effects on leukocytes at a biomaterial interface. Issue 7 (8th January 2019) - Radley, Gemma; Laura Pieper, Ina; Thomas, Bethan R.; Hawkins, Karl; Thornton, Catherine A.
Abstract: Medical devices, such as ventricular assist devices (VADs), introduce both foreign materials and artificial shear stress to the circulatory system. The effects these have on leukocytes and the immune response are not well understood. Understanding how these two elements combine to affect leukocytes may reveal why some patients are susceptible to recurrent device‐related infections and provide insight into the development of pump thrombosis. Biomaterials—DLC: diamond‐like carbon‐coated stainless steel; Sap: single‐crystal sapphire; and Ti: titanium alloy (Ti6 Al4 V) were attached to the parallel plates of a rheometer. Whole human blood was left between the two discs for 5 minutes at +37°C with or without the application of shear stress (0 s –1 or 1000 s –1 ). Blood was removed and used for complete blood cell counts, flow cytometry (leukocyte activation, cell death, microparticle generation, phagocytic ability, and reactive oxygen species [ROS] production), and the production of pro‐inflammatory cytokines. L‐selectin expression on monocytes was decreased when blood was exposed to the biomaterials both with and without shear. Applying shear stress to blood on a Sap and Ti surface led to activation of neutrophils shown as decreased L‐selectin expression. Sap and Ti blunted the LPS‐stimulated macrophage migration inhibitory factor (MIF) production, most notably when sheared on Ti. The biomaterials used here have been shown to activate leukocytes in a static environment. The introduction of shear appears to exacerbate this activation. Interestingly, a widely accepted biocompatible material (Ti) utilized in many different types of devices has the capacity for immune cell activation and inhibition of MIF secretion when combined with shear stress. These findings contribute to our understanding of the contribution of biomaterials and shear stress to recurrent infections and vulnerability to sepsis in some VAD patients as well as pump thrombosis.